TRAINING AND ASSISTANCE OF PKK GROUPS IN UTILIZING EUCALYPTUS LEAF PLANTS AS HAND SANITIZER PRODUCTS AND PROCESSING TELANG FLOWERS INTO IMPROVE THE IMMUNE SYSTEM - Dwi Setiani Sumardiko; Rini Hamsidi; Edith Frederika Puruhito; Bunga Putri Salsabillah Efendi; Marita Tri Santi (Darmabakti Cendekia: Journal of Community Service and Engagements, 2022)
Background: Until now, the COVID-19 pandemic has become a world health problem, including in Indonesia. To break the chain of transmission of the virus, the immune system and body hygiene must be maintained Objective: The purpose of this campaign is to transferred knowledge and technology to PKK group partners in Kedungsukodani Village regarding the use of eucalyptus leaves to produce natural Hand Sanitizer products and processed telang flowers into instant drinks in the form of powder that can be used daily. Method: The method used is socialization, training and mentoring Results: This activity has been carried out for one day and was attended by 30 participants, at the Kedungsukodani Village Hall in accordance with health protocols in the new normal era by paying attention to 3M. Conclusion: With the implementation of this campaign, participants can practice the knowledge that has been taught in their respective homes. It is hoped that the participants will care and help the process of handling COVID-19.